Effect of N,N-Dimethylformamide, Ethylene Glycol and Their Mixture on Cryoresistance of Canine Spermatozoa - Koshevoy, V. P.; Furda, I. V.; Egorov, M. I. (Problems of Cryobiology and Cryomedicine, 2006)
The effect of N,N-dimethylformamide (DMFA), ethylene glycol (EG) and their mixture as well on functional properties of canine spermatozoa subjected to freeze-thawing has been studied. It has been found that after freeze-thawing 20% of cells remain motile in the presence of 1M DMFA within 8hrs. It has been shown that the value of functional integrity of canine spermatozoa, cryopreserved with the protection of 1M DMFA, enables to use them in artificial fertilization. Use of cryoprotective medium based on the mixture of DMFA and EG (concentration of each cryoprotectant was 0.5M) did not positively affect motility and survival of canine spermatozoa after freeze-thawing.